Ultrafiltration based process for the recovery of polysaccharides and polyphenols from winery effluents - Giacobbo, A. (2013)
Winery effluents have a high pollution potential, especially those effluents that are obtained from the second racking. However, these effluents are rich in phenolic compounds and polysaccharides and can be potential sources for the recovery of these compounds. Therefore, a process was developed in this study to reduce the pollution potential of the winery effluents from the second racking and to recover the polyphenols and polysaccharides from the effluents by utilizing ultrafiltration (UF) and sedimentation operations. The sedimentation was optimized by varying the pH from 3.8 to 8.0, while the UF experiments were optimized by varying the transmembrane pressure from 0.5 to 4.0 bar and the feed circulation velocity from 0.44 to 0.87 ms−1. This process provided a permeate stream with a reduction in the TOC content by 56.6%, while the polyphenols and the polysaccharides in the concentrate stream were concentrated by 6 times and 5 times, respectively.